Comparative Analysis of Financial Distress Risk in Sharia Foreign Exchange Bank and Non-Foreign Exchange Sharia Bank in Indonesia in 2014-2018 Using the Method Altman Z-Score Modification - Cindi Yayang Safitri; Sholikha, Akhris Fuadatis (Wealth: Journal of Islamic Banking and Finance, 2022)
This study aims to perform a comparative analysis of predictions of financial distress at Sharia Foreign Exchange Banks and Non-Foreign Exchange Sharia Banks. This study uses the Modified Altman Z-score model to explain the prediction of financial distress at Sharia Foreign Exchange Banks and Non-Foreign Exchange Sharia Banks, then the Mann-Whitney U Test is used to show a comparative analysis of the Altman Z-score value. Data used in This research is time series data, data from 2014 to 2018. The data is obtained from the publication of each website of the Sharia Foreign Exchange Banks and Non-Foreign Exchange Sharia Banks. Sampling technique in research uses a purposive sampling method. This study uses a sample of as many as 4 Sharia Foreign Exchange Banks and 4 Non-Foreign Exchange Sharia Banks. The results showed that based on the calculation of the level of risk financial distress carried out at Sharia Foreign Exchange Banks and Non-Foreign Exchange Sharia Banks in 2014 to 2018, can be concluded that no bank predicting to experience financial distress. Average The Z-score value of the two groups of Islamic Commercial Banks is above the cut value off the risk of financial distress. The results of the comparison of financial distress risk between Sharia Foreign Exchange Banks and Non-Foreign Exchange Sharia Banks on the calculation of the Z-score and Test Mann-Whitney U test shows that there is no difference in the risk of financial distress between Sharia Foreign Exchange Banks and Non-Foreign Exchange Sharia Banks as evidenced by: The significance value is more significant than 0.025, which is 0.685.